Study of fabrication AI-Tin slag composite by powder metallurgy method - Muhammad Syazwan Abdul Manan
This final year project is about a study of fabrication AI-Tin slag composite by powder metallurgy method. Aluminum-tin slag composite have been produced by powder metallurgy (P/M) route. Aluminum (Al) and tin slag were undergo milling and sieving process where particle size <75 ℗æm and <63 ℗æm for tin slag and aluminum were obtained.